Structure-function studies of the myosin motor domain: importance of the 50-kDa cleft. - Ruppel, K M (1996)
We used random mutagenesis to create 21 point mutations in a highly conserved region of the motor domain of Dictyostelium myosin and classified them into three distinct groups based on the ability to complement myosin null cell phenotypes: wild type, intermediate, and null. Biochemical analysis of the mutated myosins also revealed three classes of mutants that correlated well with the phenotypic classification. The mutated myosins that were not fully functional showed defects ranging from ATP nonhydrolyzers to myosins whose enzymatic and mechanical properties are uncoupled. Placement of the mutations onto the three-dimensional structure of myosin showed that the mutated region lay along the cleft that separates the active site from the actin-binding domain and that has been shown to move in response to changes at the active site. These results demonstrate that this region of myosin plays a key role in transduction of chemical energy to mechanical displacement.